Citizen participation and social organizations - Díaz Pretel , José Carlos (2021)
The article aims to determine the state of the art of citizen participation and social organizations. The methodology used consisted basically of a systematic, analytical and critical review of the main theoretical foundations of the state of the art. The document contains six sections. The first deals with the collision of democracy and the conceptualization of citizen participation; the second, of the contextualization of citizen participation in the framework of a participatory democracy with co-responsibility; the third, of social networks as new scenarios for citizen participation and social groups; the fourth, of rhetorical democracy and its praxis as mechanisms of citizen participation; the fifth, of the creative interaction (co-creation) between the public administration and citizens for autonomy; and, the sixth, of citizen participation and its importance of the political model. Finally, the research conclusions are presented.